Enhancing water solubility of phytosterols through Co-amorphization with food-grade coformers - Yuxin Li; Yingting Luo; Xuening Song; Yuzhuo Wang; Simiao Liu; Fazheng Ren; Lingyan Kong; Hao Zhang (Current Research in Food Science)
Phytosterols (PS) offer significant health benefits in human diet, but its poor solubility limits its effectiveness and application. This study explored enhancing PS solubility by testing thirteen food-grade coformers, three preparation methods and proportions screening to obtain the optimal formulation. Nicotinamide (Nic) was identified as the most effective coformer. A 20:1 (w/w) PS-Nic co-amorphous (CM) mixture, prepared via freeze-drying, achieved a solubility of 1536.4 μg/mL, significantly higher than pure PS. X-ray diffraction and differential scanning calorimetry confirmed the amorphous state of the mixture. Fourier-transform infrared, Raman, and 1H NMR spectroscopies, along with molecular dynamics simulations, revealed strong intermolecular interactions between PS and Nic. The PS-Nic CM demonstrated up to 60% in vitro dissolution and release within 2 h and maintained stable after storage at 4 °C for 6 months and under accelerated conditions equivalent to 10 months at room temperature. In sum, the crystal structure of PS was altered, and formed a co-amorphous system by using Nic as the optimal ligand via lyophilization to increase solubility. These findings suggest that the PS-Nic CM system has potential applications in functional foods, offering a feasible strategy to enhance the bioavailability of PS.